Lift Force of Airfoil (NACA 0012, NACA 4612, NACA 6612) With Variation of Angle of Attack and Camber: Computational Fluid Dynamics Study - Ardany, Mariza D.; Pandiangan, Paken; Hasan, Moh. (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2021)
Airfoil is a cross section from air plane wings can affect aerodynamic performance to lift force (FL). The lift force generated by airfoil has different values due to several external and internal factors, including angle of attack, flow rate and camber. To find the lift force of airfoils with different cambers and variations angle of attack and then flow rate can use computational fluid dynamics simulation. Computational fluid dynamics is simulation on a computer that can complete systems for fluid, heat transfer and other physical processes. This research using computational fluid dynamics simulation performed by SolidWorks, with NACA airfoil type which has different camber NACA 0012, NACA 4612 and NACA 6612. The angle of attack used in research was 0o, 4o, 8o, 12o, 16o and 20o. Flow rate used in research was 20m/s, 40 m/s, 60 m/s, 80 m/s and 100 m/s. From this research will be the bigger camber can produce a greater force lift. In addition, the greater airfoil flow rate can produce a greater force lift. This research also that the connection between force lift with coefficient lift (CL) is nonlinear quadratic form.